Nationalism in History Learning: Reflections on Kampus Merdeka Learning Kurikulum Merdeka Through Modul Nusantara Program - Naredi, Hari; Saripudin, Didin; Yulifar, Leli; Sjamsuddin, Helius (Studies in Learning and Teaching, 2025)
The purpose of the study is to explore the advantages and disadvantages of the Modul Nusantara Implementation Process, Independent Student Exchange, and Knowing Nationalism in History Learning in the Context of Kurikulum Merdeka. History teaching in high schools has undergone a significant transformation. This concept encourages students to be more actively involved in managing their learning, exploring personal interests, and increasing independence. Students have the freedom to choose historical topics that interest them, explore various perspectives, and develop research and analysis skills. History teachers act as facilitators, providing guidance and support. Even though history teaching has had many breakthroughs and developments to make learning interesting, this research analyzes and explores one universal breakthrough, namely the advantages and disadvantages of the Nusantara Module implementation process, independent student exchange, and to get to know nationalism in history learning in the context of the independent curriculum. This research uses a mixed-method approach using a sequential Explanatory design. The researcher collected and analyzed quantitative data first, followed by qualitative data collection and analysis to help explain or deepen the quantitative findings. The respondents of the study were the first batch of independent exchange students from the Ministry of Education and Culture. Semi-structured questionnaires, interviews, and document analysis were used as data collection strategies. The findings show that after taking Modul Nusantara, and third, related to pride in Indonesian culture, out of 52 respondents (100%), all stated that they were proud. Through Modul Nusantara, their love for their homeland could be increased.